SCRUTINY ON BENEFITS OF TAKRA PRAYOGA AS PER CHARAKA SAMHITA - Puripanda, *S.Kamalakar; Kumar, Pawan; Vaidya, S M. (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda gives great importance to Takra as diet and as medicine. There are many different preparations mentioned the management of Agni Vikruthi, Vata and Kapha involvement conditions in our classics. In those preparations one common and most important Dravya mentioned by all Acharyas is Takra. In Charaka Samhita the usefulness of Takra is mentioned in many topics like Grahani, Arshas, Udara and mainly Vata, Kapha conditions. Different types of Takra mentioned in various disease treatment modalities like Ahara, Oushadhi, Sahapana, Anupana and Bahya Pragoya, it can be adopted in clinical practice to obtain desired benefits. Takra acts as Vata, Kapha Shamaka and it does not cause aggravation of Pitta. Takra is light for digestion hence is preferable in patients suffering from the diseases having Agni Vikruthi condition. In this paper an effort will be made to explore the Takra Prayoga mentioned in Charaka Samhita.